Al Mughni fi abwab al tawhid wa al 'adl - Abi al Hasan Abdul-Jabbar (Dar al Misriyah, 1965)
ws.jl.4-5.c.1-3,jl.6.c1-4,jl.8-9.c.1-3,jl.11.c.1-2,jl.12.c.1-4,jl.14.c.1-6,jl.15.c.1-3,jl.16.c.1,jl.20.c.1-13